Effects of resistance-based training and polyphenol supplementation on physical function, metabolism, and inflammation in aging individuals - Mathias Flensted-Jensen; Cecilie Moe Weinreich; Ann-Sofie Kleis-Olsen; Filip Hansen; Nadia Stenner Skyggelund; Jeppe Rahbek Pii; Ryan Whitlock; Marie-Louise Brødsgaard Abrahamsen; Thomas Isbrandt Petersen; Anders Karlsen; Dace Reihmane; Flemming Dela (GeroScience, 2025)
Aging is associated with declines in muscle mass, strength, aerobic capacity, and metabolic health, accompanied by increased low-grade inflammation. The purpose of this study was to assess the effects of 12 weeks of resistance training (RT) combined with minimal high-intensity interval training (HIIT), with or without polyphenol supplementation, on muscular, cardiovascular, metabolic, and inflammatory adaptations in healthy older adults. Forty-one men and women aged 55–70 years ingested either polyphenol supplementation or placebo for 30 days, then underwent 12 weeks of supervised RT combined with once-weekly HIIT, continuing polyphenol supplementation or placebo throughout. The training intervention increased whole-body and thigh lean mass, vastus lateralis cross-sectional area, type II fiber size, and muscle and functional strength (all p < 0.001). Maximal oxygen uptake significantly increased ( p = 0.0001), accompanied by reductions in heart rate and plasma lactate during submaximal exercise, as well as increases in total blood volume and hemoglobin mass ( p < 0.05). Training led to reductions in respiratory exchange ratio and plasma cortisol during exercise, which, together with decreased cholesterol levels and trends toward increased peak fat oxidation, may suggest enhanced substrate utilization. Polyphenols alone lowered cholesterol levels but had no other effects. Although no changes were observed in basal systemic or muscle inflammation, the exercise intervention attenuated the acute exercise-induced inflammatory responses of IL-10, IFN-γ, and TNF-α ( p < 0.05). These results indicate that a combined RT and minimal HIIT program improves muscular, aerobic, and metabolic health, and may improve inflammatory regulation in aging adults.